1993
DOI: 10.1128/jcm.31.11.3068-3070.1993
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cholera toxin gene in stool specimens by polymerase chain reaction: comparison with bead enzyme-linked immunosorbent assay and culture method for laboratory diagnosis of cholera

Abstract: Stool specimens obtained from 123 hospitalized patients with acute secretory diarrhea admitted to the Infectious Diseases Hospital, Calcutta, India, were examined for isolation of Vibrio cholerae 01 by direct or enrichment plating on selective media for cholera toxin (CT) by bead enzyme-linked immunosorbent assay (bead-ELISA) and for the CT gene by polymerase chain reaction (PCR). V. cholerae 01 was isolated either by direct culture or by enrichment culture from 70 stool specimens, all ofwhich gave positive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…Our previous studies on detection of the ctxA gene directly from stool samples of cholera patients have shown that rice-water stools are amenable to PCR analysis without pretreatment to remove substances that are inhibitory to the PCR assay [15,24]. This study further con¢rms our previous observation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our previous studies on detection of the ctxA gene directly from stool samples of cholera patients have shown that rice-water stools are amenable to PCR analysis without pretreatment to remove substances that are inhibitory to the PCR assay [15,24]. This study further con¢rms our previous observation.…”
Section: Discussionsupporting
confidence: 88%
“…Because of the devastating epidemic potential of O1 and O139 serogroups, the quick diagnosis and identi¢cation of the causative serogroup is important especially from a public health point of view. Realizing the need for quick diagnosis, a variety of rapid tests including co-agglutination tests [11^13], enzyme-linked immunosorbent assays [14,15] and membrane based immunoassays [16] have been developed in the recent past. Recently, Albert et al [17] have developed a polymerase chain reaction (PCR) assay using a primer pair corresponding to a chromosomal region of V. cholerae O139 for rapid detection of the serogroup from stool samples.…”
Section: Introductionmentioning
confidence: 99%
“…However, several problems are encountered with culturing methods, including the presence of viable but non-culturable cells, loss of viability of bacteria after collection, dif®culties in isolation from biocontaminated samples and the time required for culture and con®rmation, which can be several days (Wright et al 1993). To avoid these problems, different methods based on molecular biology techniques have been developed, with those based on DNA ampli®cation being the most rapid and sensitive (Garret et al 1993;Ramamurthy et al 1993). Nevertheless, ampli®ed products are seldom detected by direct visualization in ethidium bromide-stained agarose gels, but rather by Southern blot or dot-blot hybridization (Koch et al 1993;Wright et al 1993;Nair et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, diagnostic laboratories have been concerned with reducing the time required for the diagnosis of Salmonella infections and a more rapid and sensitive method for detection and identification of Salmonella serovars from clinical specimens is needed. Amplification of DNA sequences unique to an organism using the PCR improves both the speed of detection and the level of sensitivity at which organisms can be detected (Buffone et al 1991;Ramamurthy et al 1993) and has been increas-ingly used to identify several bacterial species from food and clinical samples (Stone et al 1994). Another advantage is that PCR is not dependent on the utilization of a substrate or the expression of antigens, thereby circumventing phenotypic variations in biochemical patterns and lack of detectable antigens (Hoorfar et al 1999).…”
Section: Introductionmentioning
confidence: 99%